UN TRATADO DE LA ÉPOCA ARCAICA (ALIANZA ENTRE ÉLIDE Y HEREA?). ANÁLISIS DEL EPÍGRAFE EN EL ÁMBITO DE LAS INSTITUCIONES DEL MUNDO GRIEGO - Fernández Nieto, Francisco Javier (Antigüedad y Cristianismo, 1995)
Our study explains the historical background of the alliance between Eleans and Heraeans, c. 500 a.c., and anaiyses the evolution of the different Greek institutions in relation to the agreements of Symmachia, with the purpose of making clear the reach and meaning of the clauses found and concisely enunciated in the text of the Treaty. (...)